Finite element modeling for analysis vibration of large turbo machinery - Ngo, Van Thanh; Xie, Danmei; Le, Hoai Duc (Vietnam Journal of Science and Technology, 2014)
Recently, finite elements method (FEM) has been used most popular for analysis of stress, vibration, heat flow and many other phenomena. With the increase in computing power, FEM is wider used for the static and dynamic analysis of rotor bearing system. In this paper, the lateral vibration of large turbo machinery is studied. The FEM model is created and the eigenvalues and eigenvectors are calculated and analyzed to find natural frequencies, critical speeds, mode shapes and unbalance responses. Then critical and mode shapes are determined. Finally, responses of unbalance force are analyzed and compared in case of isotropic bearings and anisotropic bearings.